A 10,300-year-old permafrost core from the active rock glacier Lazaun, southern Otztal Alps (South Tyrol, northern Italy) - Krainer, Karl; Bressan, David; Dietre, Benjamin; Haas, Jean N.; Hajdas, Irka; Lang, Kathrin; Mair, Volkmar; Nickus, Ulrike; Reidl, Daniel; Thies, Hansjörg; Tonidandel, David (Quaternary Research, 2015)
ISSN:0033-5894